2014
DOI: 10.1016/j.diabres.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the short- and long-term cost-effectiveness of starting biphasic insulin aspart 30 in insulin-naïve people with poorly controlled type 2 diabetes

Abstract: Starting BIAsp 30 in people with type 2 diabetes in the A(1)chieve study was found to be cost-effective across all country settings at 1- and 30-year time horizons, and usefully increased predicted life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…These results reinforce the value of initiating or optimizing treatment sooner rather than later in patients not reaching desired glycemic targets. Finally, new health-economic studies are also in line with previous work and now demonstrate that, projected over a 30-year horizon, BIAsp 30 is cost effective versus BHI 30, NPH insulin, or IGlar (in India, Saudi Arabia, and Indonesia) for both insulin-naïve [ 42 ] and insulin-experienced [ 43 ] patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results reinforce the value of initiating or optimizing treatment sooner rather than later in patients not reaching desired glycemic targets. Finally, new health-economic studies are also in line with previous work and now demonstrate that, projected over a 30-year horizon, BIAsp 30 is cost effective versus BHI 30, NPH insulin, or IGlar (in India, Saudi Arabia, and Indonesia) for both insulin-naïve [ 42 ] and insulin-experienced [ 43 ] patients.…”
Section: Discussionsupporting
confidence: 80%
“…The economic impact of switching from BHI 30, IGlar, or NPH insulin was projected over a 30-year horizon, and the impact on quality of life was projected over 1 year. BIAsp 30 was projected to be cost effective versus the other treatments over both the short (1 year) and long (30 years) term in insulin-naïve [ 42 ] and insulin-experienced patients [ 43 ].…”
Section: Cost Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…These two instruments have been proved valid in many contexts, and across many health conditions in many countries [ 6 , 8 16 ], including Indonesia [ 17 , 18 ]. In Indonesia, both questionnaires are increasingly being used in different types of investigations, for example in the measurement of quality of life in different patient groups [ 19 22 ] and in cost-effectiveness studies [ 23 25 ]. Thus far, no investigation has measured the stability over time of both questionnaires when measuring the HRQOL of the Indonesian general population: the test-retest reliability.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio values used for different discount rates to calculate undiscounted outcomes for the rest of the 31 studies (59/124 data points) can be found in Supplementary Material 4. One study [ 33 ] with four comparators was excluded from the QALYs regression analysis because it involved a large utility change in year 1 (0.152–0.312) as a direct treatment effect stemming from the intervention. This makes the relationship between HbA 1c and QALY gain in this study not comparable to others, as other studies generally assumed changes in utility were mediated through changes in other risk factors such as BMI.…”
Section: Resultsmentioning
confidence: 99%